Characterization and Chemical Composition Analysis of Tea Tree (Meleuca alternifolia) Leaf Hydrosols Growing on Lombok Island - Baiq Riyankati; Surya Hadi; Sri Seno Handayani (Jurnal Penelitian Pendidikan IPA, 2022)
Tea tree is an essential oil-producing plant from Australia which is also found growing in several parts of Indonesia, including the island of Lombok. So far, tea tree essential oil producers on the island of Lombok do not utilize by-products in the form of hydrosol (distilled water) produced in the process of making essential oils. In this study, the characterization and analysis of the chemical composition of the hydrosol of tea tree leaves growing on the island of Lombok was carried out. The characteristic aroma of hydrosol is similar to that of tea tree essential oil. The results of the GC-MS analysis also showed that the hydrosol of tea tree leaves also had similarities with the essential oil, composed of major compounds in the form of trans-caryophyllene (28.58%), limonene (13.98%) and terpinen-4-ol (16.27%). Other compounds detected were -pinene (4.14%), -pinene (6.50%), -myrcene (8.09%), -terpineol (10.10%) and -terpinene (5.77%).